Strain tunable intrinsic ferromagnetic in 2D square CrBr2 - Fei Li (AIP Publishing LLC, 2021)
Two-dimensional intrinsic magnetic materials with high Curie temperature (Tc) coexisting with 100% spin polarization are highly desirable for realizing promising spintronic devices. In the present work, the intrinsic magnetism of monolayer square CrBr2 is predicted by using first-principles calculations. The monolayer CrBr2 is an intrinsic ferromagnetic half-metal with the half-metallic gap of 1.58 eV. Monte Carlo simulations based on the Heisenberg model estimate Tc as 212 K. Furthermore, the large compressive strain makes CrBr2 undergo ferromagnetic–antiferromagnetic phase transition when the biaxial tensile strain larger than 9.3% leads to the emergence of semiconducting electronic structures. Our results show that the intrinsic half-metal with a high Tc and controllable magnetic properties endow monolayer square CrBr2 as a potential material for spintronic applications.